The Surrendered Reflections by a Son of Shining Path - Agüero, José Carlos (Duke University Press, 2021)
The Surrendered is Peruvian public intellectual José Carlos Agüero's reflections on his parents-who were executed by the state for being Shining Path militants-as well as the legacies of the Peruvian internal armed conflict and the possibility for forgiveness and reconciliation in the face of hate.